Algebra and Trigonometry 10th Edition

Published by Cengage Learning
ISBN 10: 9781337271172
ISBN 13: 978-1-33727-117-2

Chapter 4 - 4.4 - Translations of Conics - 4.4 Exercises - Page 349: 95a



Work Step by Step

We need to write $b$ in terms of $c$. $b^2=a^2-c^2$ $c=ae$, Therefore, $b^2=a^2-(ae)^2=a^-a^2e^2$ or, $b^2=a^2(1-e^2)$ The standard form of the equation of an ellipse is: $\dfrac{(x-h)^2}{a^2}+\dfrac{(y-k)^2}{b^2}=1$ or, $\dfrac{(x-h)^2}{a^2}+\dfrac{(y-k)^2}{a^2(1-e^2)}=1$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.